Figuring Jesu s the power of rhetorical figures of speech in the Gospel of Luke - Reich, Keith A. (Biblical Interpretation Series, 2011)
This book examines the Lukan Jesus' speech, specifically his use of rhetorical figures of speech, as a means of determining Luke's message and rhetorical strategy of persuasion. Classical rhetoric dominated both Greco-Roman higher education and public discourse in the first-century Mediterranean world. Thus, both authors and audiences in this era were familiar with the rudiments of rhetoric whether or not they had formal rhetorical training. Rhetorical figures of speech would have been easily recognized by an ancient audience, arresting their attention. Luke used figures of speech on the lips of Jesus as a means of persuading his audience of his role-reversing message that threatened to turn the religious, political, social, and economic systems of the Roman Empire upside-down.